Tanytarsini (Diptera: Chironomidae) collected during Polish expeditions to North Korea - Giłka, Wojciech; Gadawski, Piotr (Zootaxa, 2022)
This systematic review of non-biting midges of the tribe Tanytarsini is based on materials collected during Polish scientific expeditions to North Korea. Stempellina radoszkowskii sp. nov. is described. Brief illustrated redescriptions of adult males of further eight species, for the first time recorded from North Korea, are presented: Cladotanytarsus (Cladotanytarsus) sinjongensis Ree et Kim, 1988, Micropsectra joganplumosa Sasa et Okazawa, 1991, M. jokatertia Sasa et Ogata, 1999, Tanytarsus iriolemeus Sasa et Suzuki, 2000, T. oyamai Sasa, 1979, T. takahashii Kawai et Sasa, 1985, T. tamadecimus Sasa, 1980 and T. tamaundecimus Sasa, 1980. New synonyms are proposed: Micropsectra tonewdeea Sasa et Tanaka, 2002, syn. nov. [=Micropsectra atrofasciata (Kieffer, 1911)]; Micropsectra tusimalemea Sasa et Suzuki, 1999, syn. nov., M. tusimamenea Sasa et Suzuki, 1999, syn. nov., M. tusimaquerea Sasa et Suzuki, 1999, syn. nov. [=Micropsectra joganplumosa Sasa et Okazawa, 1991], and several further synonyms of the species reviewed are suggested. An annotated checklist of Tanytarsini so far reported from North Korea is given. A historical note on Polish scientific expeditions to Korea is also included.